2022
DOI: 10.7185/geochemlet.2223
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of benthic flux of REEs on continental shelves: implications for oceanic budgets

Abstract: Rare earth elements (REEs) are powerful tools to track oceanic biogeochemical processes. However, our understanding of REE sources is incomplete, leading to controversial interpretations regarding their oceanic cycling. Continental margin sediments are often assumed to be a major source, but the sediment pore water data required to understand the processes controlling that potential source are scarce. Here, we measure and compile pore water and estuarine REE data from the Changjiang (Yangtze) estuary-East Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This suggests that perhaps too much emphasis has been put on a widespread abyssal benthic flux to resolve the Nd paradox, and it may be that shallower and marginal regions pose a larger in magnitude and more distinct Nd source to seawater as opposed to an open-ocean benthic source. Recent pore water measurements by Deng et al (2022) on the East China continental shelf revealed larger benthic fluxes across the dynamic hydraulic environment of the continental shelf compared to deep pore water, which acted as a sink, likely due to authigenic precipitation. As such, spatial variations in the benthic flux are likely affected by multiple complex depth-related processes, although deep-ocean regions may still dominate the total area-integrated benthic flux.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that perhaps too much emphasis has been put on a widespread abyssal benthic flux to resolve the Nd paradox, and it may be that shallower and marginal regions pose a larger in magnitude and more distinct Nd source to seawater as opposed to an open-ocean benthic source. Recent pore water measurements by Deng et al (2022) on the East China continental shelf revealed larger benthic fluxes across the dynamic hydraulic environment of the continental shelf compared to deep pore water, which acted as a sink, likely due to authigenic precipitation. As such, spatial variations in the benthic flux are likely affected by multiple complex depth-related processes, although deep-ocean regions may still dominate the total area-integrated benthic flux.…”
Section: Resultsmentioning
confidence: 99%
“…The decoupled nature of marine [Nd] and ε Nd , which is yet to be fully understood, and new emerging observations (e.g. Stichel et al, 2020;Lagarde et al, 2020;Paffrath et al, 2021;Deng et al, 2022) emphasise the critical need to progress our understanding of modern marine Nd cycling in the light of continued use of ε Nd as a valuable tracer of ocean circulation. In this context, Nd-isotopeenabled ocean models remain an effective way to understand seawater measurements and to progress with testing and constraining processes governing marine Nd cycling, which can then feedback key information to the wider GEOTRACES and ocean tracer modelling community.…”
Section: Introductionmentioning
confidence: 99%
“…Overlying bottom water was first drained and filtered. Pore-water was separated using methods previously described in detail ( 31 , 50 ) at ~cm resolution, either by centrifuging sliced core sediment under anaerobic conditions followed by filtration (Baltic Sea samples: 0.2-μm filters and Mexico-California margin samples: 0.45-μm filters) or by in situ extraction via precleaned Rhizon samplers (East China Sea samples: 0.15-μm filters). Water samples were acidified for storage (pH ≤ 2).…”
Section: Methodsmentioning
confidence: 99%
“…We developed a procedure that can separate three components, which are, salt matrix, Be, and other trace metals such as REE on the same sample, optimizing the usage of precious pore-water samples. To do so, we coupled a well-established REE preconcentration protocol ( 50 , 51 ) with an additional procedure for the preconcentration of Be from the remaining seawater matrix ( 14 , 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…frontiersin.org proxies to reveal the source, genesis, and sedimentary environment (Jiang et al, 2019;Gallello et al, 2021;Romero et al, 2021;Zhang X et al, 2021;Deng et al, 2022a).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%